2013
DOI: 10.1371/journal.pone.0069728
|View full text |Cite
|
Sign up to set email alerts
|

Unit Cost of Medical Services at Different Hospitals in India

Abstract: Institutional care is a growing component of health care costs in low- and middle-income countries, but local health planners in these countries have inadequate knowledge of the costs of different medical services. In India, greater utilisation of hospital services is driven both by rising incomes and by government insurance programmes that cover the cost of inpatient services; however, there is still a paucity of unit cost information from Indian hospitals. In this study, we estimated operating costs and cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
91
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 17 publications
14
91
7
1
Order By: Relevance
“…This is the first study that estimated the operating costs and unit costs of hospital services in a big public urban hospital in Jordan. In line with findings from the previous two hospital autonomy reports from Jordan in 2002 (As‐Sayaideh et al , ; Banks et al , ) and reports from a number of developing countries (Vander Plaetse et al , ; Saksena et al , ; Chatterjee et al , ; Younis et al , ),we found that 50% and 17% of the hospital expenditures were consumed by inpatient and outpatient care centres respectively.…”
Section: Discussionsupporting
confidence: 92%
“…This is the first study that estimated the operating costs and unit costs of hospital services in a big public urban hospital in Jordan. In line with findings from the previous two hospital autonomy reports from Jordan in 2002 (As‐Sayaideh et al , ; Banks et al , ) and reports from a number of developing countries (Vander Plaetse et al , ; Saksena et al , ; Chatterjee et al , ; Younis et al , ),we found that 50% and 17% of the hospital expenditures were consumed by inpatient and outpatient care centres respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Chatterjee et al also found that private hospitals in India had lower levels of staffing costs. The main reasons for the lower proportion of staffing in private hospitals is that they offer salary structures below the market rate, have more flexibility in using staff, and greater dependence on part‐time contract staff …”
Section: Discussionmentioning
confidence: 99%
“…The results of a study conducted by Chatterjee, Levin and Laxminarayan (2013) show "One reason for the overhead high cost at the outpatient and inpatient departments of the privilege can be focused on cases, which ones may be few." 13 Reason for the high the overall costs of outpatient and hospitalization can be due to some special cases that should get the focus of the hospital, but the cases are likely to be few.…”
Section: Discussion Direct Cost Charges In Unit Cost Calculation Diagmentioning
confidence: 99%